Action mode of cranberry anthocyanin on physiological and morphological properties of Staphylococcus aureus and its application in cooked meat. (April 2021) - Gong, Shaoying; Fei, Peng; Sun, Qi; Guo, Ling; Jiang, Liange; Duo, Kai; Bi, Xue; Yun, Xueqi
Abstract: This study researched the action mode of cranberry anthocyanin (CA) against Staphylococcus aureus and the effect of CA on the counts of S. aureus and the quantity of cooked meat during storage. The antibacterial effect was assessed by minimum inhibitory concentration (MIC) and survival populations of S. aureus strains after CA treatments. The changes in intracellular adenosine 5′-triphosphate (ATP) concentration, cell membrane potential, content of bacterial protein and cell morphology were analyzed to reveal possible action mode. Application potentials of CA as antimicrobial agent were assessed during storage of cooked pork and beef. The result showed that the MIC of CA against S. aureus strains was 5 mg/mL. Approximately 8 log CFU/mL of S. aureus strains can be completely inhibited after treatment with 2.0 MIC of CA for 0.5 h. Treatments of CA resulted in lower intracellular ATP and soluble protein levels, damaged membrane structure and leakage of cytoplasmic. Application of CA on cooked pork and beef caused a significant decrease in S. aureus counts and pH values, and color-darkening compared with control samples. These findings demonstrated that CA played an effective antimicrobial against S. aureus and had a potential as natural preservative to inhibit the growth of food pathogens. Highlights: Cranberry anthocyanin (CA) can against Staphylococcus aureus. CA changed the physiology and morphology of S. aureus. CA damaged cell membrane and bacteria protein of S. aureus. CA caused the decrease of S. aureus count in cooked meat.